12th ACM Conference on Web Science 2020
DOI: 10.1145/3394231.3397900
|View full text |Cite
|
Sign up to set email alerts
|

Gender Classification and Bias Mitigation in Facial Images

Abstract: Gender classi cation algorithms have important applications in many domains today such as demographic research, law enforcement, as well as human-computer interaction. Recent research showed that algorithms trained on biased benchmark databases could result in algorithmic bias. However, to date, li le research has been carried out on gender classi cation algorithms' bias towards gender minorities subgroups, such as the LGBTQ and the non-binary population, who have distinct characteristics in gender expression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Wu et al [85] collected two benchmark datasets: the Inclusive Benchmark Database (IBD), and Non-binary Gender Benchmark Database (NGBD) 24 . IBD contains 12,000 images of 168 different subjects, 21 of which identify as LGBTQ.…”
Section: Datasets Buolamwini and Gebrumentioning
confidence: 99%
See 2 more Smart Citations
“…Wu et al [85] collected two benchmark datasets: the Inclusive Benchmark Database (IBD), and Non-binary Gender Benchmark Database (NGBD) 24 . IBD contains 12,000 images of 168 different subjects, 21 of which identify as LGBTQ.…”
Section: Datasets Buolamwini and Gebrumentioning
confidence: 99%
“…Thus, the database contains multiple gender identities (namely: non-binary, genderfluid, genderqueer, gender non-conforming, agender, gender neutral, gender-less, third gender, and queer ). The authors themselves identify two major risks of label bias: first, "Gender identity has its multifaceted aspects that a simple label could not categorize" [85] (the authors identify the problem of modelling gender as a continuum as a direction for future work); and, second, "Gender is a complex socio-cultural construct and an internal identity that is not necessarily tied to physical appearances." [85].…”
Section: Datasets Buolamwini and Gebrumentioning
confidence: 99%
See 1 more Smart Citation
“…There has been an increased desire for privacy regarding facial analysis, and demographic data is usually considered a sensitive attribute. Facial analysis, such as gender classification, has also been seen to have high error rates in LGBTQ+, and non-binary individuals [16]. Moreover, in [1], Qiu et al, found that false classifications of gender correlate with a false rejection of a true matching.…”
Section: Introductionmentioning
confidence: 99%
“…Bias and mitigation strategies in facial analysis have attracted increasing attention both from the general public and the research communities. For example, many studies have investigated bias and mitigation strategies for face recognition [5,12,13,14,35,38,41], gender recognition [8,12,43,50], age estimation [6,8,12,16,43], kinship verification [12] and face image quality estimation [44]. However, bias in facial expression recognition has not been investigated, except for [9,49], that only focussed on the task of smiling/non-smiling using the CelebA dataset.…”
Section: Introductionmentioning
confidence: 99%